Phosphorylation of α-Actinin 4 upon Epidermal Growth Factor Exposure Regulates Its Interaction with Actin - Shao, Hanshuang (American Society for Biochemistry and Molecular Biology, 2010)
The ubiquitously expressed family of α-actinins bridges actin filaments to stabilize adhesions, a process disrupted during growth factor-induced migration of cells. During the dissolution of the actin cytoskeleton, actinins are phosphorylated on tyrosines, although the consequences of this are unknown. We expressed the two isoforms of human α-actinin in murine fibroblasts that express human epidermal growth factor receptor (EGFR) and found that both α-actinin 1 (ACTN1) and α-actinin 4 (ACTN4) were phosphorylated on tyrosine residues after stimulation with EGF, although ACTN4 was phosphorylated to the greater extent. This required the activation of Src protein-tyrosine kinase and p38-MAPK (and phosphoinositide trisphosphate kinase in part) but not MEK/ERK or Rac1, as determined by inhibitors. The EGF-induced phosphorylation sites of ACTN4 were mapped to tyrosine 4, the major site, and tyrosine 31, the minor one. Truncation mutagenesis showed that the C-terminal domains of ACTN4 (amino acids 300–911), which cross-link the actin binding head domains, act as an inhibitory domain for both actin binding and EGF-mediated phosphorylation. These two properties were mutually exclusive; removal of the C terminus enhanced actin binding of ACTN4 mutants while limiting EGF-induced phosphorylation, and conversely EGF-stimulated phosphorylation of ACTN4 decreased its affinity to actin. Interestingly, a phosphomimetic of tyrosine 265 (which can be found in carcinoma cells and lies near the K255E mutation that causes focal segmental glomerulosclerosis) demonstrated increased actin binding activity and susceptibility of ACTN4 to calpain-mediated cleavage; this variant also retarded cell spreading. Remarkably, either treatment of cells with low concentrations of latrunculin A, which has been shown to depolymerize F-actin, or the deletion of the actin binding domain (100–252 amino acids) of ACTN4Y265E restored EGF-induced phosphorylation. An F-actin binding assay in vitro showed that Y4E/Y31E, a mimetic of diphosphorylated ACTN4, bound F-actin slightly compared with wild type (WT). Importantly, the EGF-mediated phosphorylation of ACTN4 at tyrosine 4 and 31 significantly inhibited multinucleation of proliferating NR6WT fibroblasts that overexpress ACTN4. These results suggest that EGF regulates the actin binding activity of ACTN4 by inducing tyrosyl-directed phosphorylation.